PENGGUNAAN PENDEKATAN CTL UNTUK MENINGKATAN HASIL BELAJAR MATEMATIKA DI KELAS V SD - Faridatul Umi; Taufina Taufina (Universitas Negeri Medan, 2020)
This study aims to improve mathematics learning outcomes of fifth grade elementary school 05 Air Tawar Barat with a Contextual Teaching And Learning approach. This research is a classroom action research consisting of II cycles with research subjects of fifth grade students The results of the study occurred an increase in each variable in each cycle, where: a) planning the first cycle of 82.14 increased in the second cycle 92.85, b) the implementation of aspects of the first cycle teacher 80.35 increased in the second cycle 92.85, c) the implementation of aspects of the first cycle students 71.42 increased in the second cycle 89.28, d) the learning outcomes of the first cycle students 77.70 increased in the second cycle 88.08. The Contextual Teaching And Learning Approach is proven to be able to improve the quality of Mathematics learning in fifth grade SD Negeri 05 Air Tawar Barat.Keywords: CTL, learning outcomes, Mathematics